(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The constitution is referred to in the constitution of democratic nations as the supreme andhighest national legislation, and it serves to safeguard citizens’ rights. The Constitutional law serves asthe source of authority for all other legislation in the country. The rule of law is crucial to society. Theidea of law is always evolving. Laws are passed by the legislative, carried out by the executive branch,and reviewed by the court prior to passage utilizing the judicial review authority. The Constitutionrequires that legislation be examined for legitimacy. Because of this, several nations today haveproudly included judicial review into their national constitutions